2014
DOI: 10.1038/bmt.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

Differences in health behaviour between recipients of allogeneic haematopoietic SCT and the general population: a matched control study

Abstract: Little is known of health-relevant behaviour among long-term survivors of haematological disorders treated with haematopoietic SCT. This comparative cross-sectional multicentre study aimed (1) to explore the prevalence of selected behaviours in this group and (2) to compare them with those of the general population. Self-reported data of 376 survivors (mean age: 50.4 (s.d. = 12.8); median 7 years postallogeneic SCT (interquartile range (IQR) = 8.9; range 1-33) were compared with controls derived from the Swiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…In general, adult HCT survivors’ participation in unhealthy behaviors seems equal to or lower than that of other populations, with predictors of unhealthy behaviors including younger age, less education, and lack of health insurance (138). Smoking rates are similar to matched controls (139), but significantly lower than that of siblings (7% vs. 13%) (138, 139) and population-based controls (134). One study reported that 15% of HCT survivors restart smoking against the advice of their physicians (106).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…In general, adult HCT survivors’ participation in unhealthy behaviors seems equal to or lower than that of other populations, with predictors of unhealthy behaviors including younger age, less education, and lack of health insurance (138). Smoking rates are similar to matched controls (139), but significantly lower than that of siblings (7% vs. 13%) (138, 139) and population-based controls (134). One study reported that 15% of HCT survivors restart smoking against the advice of their physicians (106).…”
Section: Resultsmentioning
confidence: 69%
“…One study reported that 15% of HCT survivors restart smoking against the advice of their physicians (106). Alcohol use over the recommended 0–1 drinks per day is lower in survivors than matched controls, and lower than that of siblings (139), and weekly consumption is lower than population-based controls (134). Data on the use of sun protection are limited but reveal that survivors use sun protection more regularly than population-based controls (134).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…AUD has previously been shown to contribute to medication noncompliance in various chronic illnesses [33, 34]. While suboptimal medication compliance has been observed in up to two-thirds of long-term survivors following allogeneic HCT [35], studies on patterns of medication compliance in the early post-transplant period are lacking.…”
Section: Discussionmentioning
confidence: 99%